Potential therapeutic target for polysaccharide inhibition of colon cancer progression - Fan, Jiawei; Zhu, Jianshu; Zhu, He; Zhang, Yinmeng; Xu, Hong (Frontiers in Medicine, 2024)
In recent years, colon cancer has become one of the most common malignant tumors worldwide, posing a great threat to human health. Studies have shown that natural polysaccharides have rich biological activities and medicinal value, such as anti-inflammatory, anti-cancer, anti-oxidation, and immune-enhancing effects, especially with potential anti-colon cancer mechanisms. Natural polysaccharides can not only protect and enhance the homeostasis of the intestinal environment but also exert a direct inhibition effect on cancer cells, making it a promising strategy for treating colon cancer. Preliminary clinical experiments have demonstrated that oral administration of low and high doses of citrus pectin polysaccharides can reduce tumor volume in mice by 38% (p < 0.02) and 70% (p < 0.001), respectively. These results are encouraging. However, there are relatively few clinical studies on the effectiveness of polysaccharide therapy for colon cancer, and ensuring the effective bioavailability of polysaccharides in the body remains a challenge. In this article, we elucidate the impact of the physicochemical factors of polysaccharides on their anticancer effects and then reveal the anti-tumor effects and mechanisms of natural polysaccharides on colon cancer. Finally, we emphasize the challenges of using polysaccharides in the treatment of colon cancer and discuss future applications.